Trehalose Inhibits Inflammatory Responses through Mitochondrial Reprogramming in RAW 264.7 Macrophages - Seungmin Yu; Hyejeong Park; Wooki Kim (MDPI AG, 2023)
Studies reported the beneficial effects of trehalose on metabolic syndromes, hyperlipidemia, and autophagy, but its action mechanisms are still poorly understood. Even though trehalose is digested by disaccharidase and absorbed in the intestine, intact molecules encounter immune cells which form a solid balance between the allowance of nutritive substances and the removal of harmful pathogens. In this regard, the polarization of intestinal macrophages into an anti-inflammatory phenotype through metabolic regulation is emerging as a therapeutic strategy for the prevention of gastrointestinal inflammation. The current study investigated the effects of trehalose on immunological phenotypes, energy metabolism, and LPS-induced macrophage mitochondrial functioning. Results indicate that trehalose reduces prostaglandin E2 and nitric oxide, which are inflammatory mediators of LPS-induced macrophages. In addition, trehalose further significantly suppressed inflammatory cytokines and mediators via energy metabolism reprogramming towards M2-like status in LPS-stimulated macrophages.